Population dynamics of Oligonychus ilicis (McGregor, 1917) (Acari: Tetranychidae) in coffee plants and of their associated phytoseiids - Franco, Renato André (2008)
Oligonychus ilicis (McGregor, 1917) (Acari: Phytoseiidae) is considered one of the main phytophagous mites of coffee plants (Coffea spp.). Although not considered as principal, it was already referred as the second in importance for the Conillon coffee plant, Coffea canephora Pierre & Froehner. It is commonly in equilibrium, probably due to the presence of natural enemies, among them predatory mites belonging to the Phytoseiidae family. This work had as objectives to evaluate the O. ilicis population dynamics through the months of the year, the phytoseiids associated, and the spatial distribution of those mites in coffee plants. Studies were carried in a 1.3 ha coffee field located at EPAMIG, Lavras, Minas Gerais. Biweekly, ten leaves of superior, medium and inferior thirds (five leaves from each plant side) were randomly sampled from ten plants. The appraised leaves were removed from the third or fourth pair from the branch extremity. O. ilicis occurred along the whole period, being found in larger number of eggs than post-embryonic phases. Number of eggs in the medium and inferior parts of the plants was bigger than in the superior part. The periods of larger occurrence of O. ilicis coincided with the low pluvial precipitation time. Five species of predatory mites were found: Iphiseiodes zuluagai Denmark & Muma, 1972, Amblyseius herbicolus (Chant, 1959), Euseius citrifolius Denmark & Muma, 1970, Euseius concordis (Chant, 1959) and Euseius alatus DeLeon, 1966. The most abundant species was I. zuluagai, representing 72.4% of the phytoseiids collected and occurring during all the studied period.